Effect of time delay on the derivative of information dynamical upper bound of the time entropy in a stochastic system - 张敏敏 王参军 梅冬成 (中国物理：英文版, 2011)
The effects of the time delay on the upper bound of the time derivative of information entropy are investigated in a time-delayed dynamical system driven by correlated noise. Using the Markov approximation of the stochastic delay differential equations and the Schwartz inequality principle, we obtain an analytical expression for the upper bound UB（t） of the time derivative of the information entropy. The results show that there is a critical value of T （delay time）, and UB（t） presents opposite behaviours on difference sides of the critical value. For the case of the weak additive noise, T can induce a reentrance transition. Delay time T also causes a reversal behaviour in UB（t）-λplot, where λ denotes the degree of the correlation between the two noises.